MyoD, myogenin and proliferating cell nuclear antigen expression in growing Nile tilapia (Oreochromis niloticus L.) - Aguiar, Danilo Henrique [UNESP]; Bock, Claudio; Padovani, Carlos Roberto [UNESP]; Dal Pai-Silva, Maeli [UNESP] (Wiley-Blackwell, 2008)
In the present study, immunohistochemical and morphometric analysis was used to characterize variations in muscle growth performance during muscle fibre recruitment and hypertrophy. As in fisheries, fish were classified into four age stages: alevin 35 days (0.65 +/- 0.08 g); juvenile 60 days (13.67 +/- 1.35 g); adult 90 days (73.18 +/- 4.70 g) and adult 190 days (349.76 +/- 34.62 g). The number of nuclei expressing MyoD and myogenin was similar in alevin, juvenile and adult 90 days; however, in adult 190 days, the number of nuclei expressing myogenin was higher than the number expressing MyoD. The number of proliferating cell nuclear antigen-stained nuclei in each stage was higher than MyoD and myogenin staining with peaks in alevin and adult 90 days. These data suggest that growth per se stimulated cellular proliferation and nuclei accretion of Nile tilapia muscle fibres in alevin, juvenile and adult 90 days. Muscle fibre differentiation was more pronounced in adult 190 days.
Keywords: skeletal muscle growth; myogenic regulatory factors; Nile tilapia